ADHD impacted by sulfotransferase (SULT1A) inhibition from artificial food colors and plant-based foods - Eagle, Ken (Physiology & behavior, 2014)
Five recent reviews have analyzed trials on the association between artificial food colors and ADHD; the 50 underlying studies and the reviews in aggregate were inconclusive. Recent work has shown human in vivo SULT1A inhibition leading to incremental catecholamines, and an inverted-U relationship between brain catecholamines and proper functioning of the prefrontal cortex where ADHD behavior can arise. This study re-examined the same underlying trials for evidence that SULT1A inhibitors were in the placebos and other inactive foods, that these “inactive” materials were symptomatic, and that ADHD symptoms exhibited an inverted-U response to SULT1A inhibition. Nearly all the underlying diets, and many placebos and delivery vehicles, were found to contain SULT1A inhibitors. Eight publications provided evidence of ADHD symptoms caused by the “inactive” materials containing SULT1A inhibitors. Ten studies showed additional SULT1A inhibitors reducing the symptoms of some subjects. SULT1A inhibitors in foods, including natural substances and artificial food colors, have a role in ADHD that can both worsen or improve symptoms. Mechanistically, SULT1A enzymes normally deactivate catecholamines, especially dopamine formed in the intestines; SULT1A inhibition can influence brain catecholamines through the intermediary of plasma tyrosine levels, which are influenced by dopamine inhibition of intestinal tyrosine hydroxylase. Biochemical measurements focused on SULT1A activity and plasma tyrosine concentrations are proposed for future work. •SULT1A inhibition in the gut can increase plasma tyrosine and brain dopamine.•Artificial colors are SULT1A inhibitors, as are many natural polyphenols in foods.•Prior ADHD trials were compromised by including multiple SULT1A inhibitors.•Prior trials show evidence of SULT1A inhibition causing ADHD symptoms.•Prior trials support an inverted-U ADHD response to SULT1A inhibition.